2003
DOI: 10.1117/12.459142
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric and internal turbulence measured on the Very Large Telescope Interferometer with VINCI

Abstract: In March 2001, the commissioning instrument of the VLTI, VINCI, succeeded in obtaining its first fringes by linking two 40cm aperture siderostats on a 16m baseline. During the first year of operation, thousands of interferometric observations on different baselines were carried out, with the technical goal of characterizing this complex system. We report in this paper these first measurements and estimate the main parameters of the atmospheric and internal turbulence along the complete light path. We first ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…A method described in (2) permits to estimate the wavefront coherence time from a combination of ground based seeing measurements and general circulation data. An excellent agreement was found with VLT interferometer atmospheric phase fluctuations (3). The data summarized in Table 1 show that the ratio between existing observatories and a reference site belonging the inter tropical belt where no jet stream is present is about 2 on average and up to 5 on some months.…”
Section: Tropospheric Flow As a New Parameter For Elt Sitessupporting
confidence: 68%
“…A method described in (2) permits to estimate the wavefront coherence time from a combination of ground based seeing measurements and general circulation data. An excellent agreement was found with VLT interferometer atmospheric phase fluctuations (3). The data summarized in Table 1 show that the ratio between existing observatories and a reference site belonging the inter tropical belt where no jet stream is present is about 2 on average and up to 5 on some months.…”
Section: Tropospheric Flow As a New Parameter For Elt Sitessupporting
confidence: 68%
“…Unfortunately, the data are too noisy to infer a meaningful auto-correlation function and model its impact on the result. However, we know that the observing cadence (∼ 1 s) is significantly slower than the typical interferometric coherence time (∼ 100 ms in the IR, see Perrin 1997;di Folco et al 2003;Glindemann 2011) and atmospheric turbulence time τ0 (∼ 10 ms in the IR). So, we expect little correlation from the differential atmospheric piston and fibre injection variations.…”
Section: Baseline-dependent "Statistical" Errorsmentioning
confidence: 99%
“…Detailed studies of the properties of atmospheric piston can be found for example in Linfield et al (2001) andDi Folco et al (2002). When a dedicated fringe tracking instrument becomes available on the VLTI (e.g.…”
Section: Piston Effectmentioning
confidence: 99%